Clinicopathological and Molecular Characteristics of Intraosseous Rhabdomyosarcoma Involving Head and Neck Region: A Systematic Review and Meta-Analysis. (May 2023) - Sivakumar, N.; Sharma, Pooja; Chandra, Shaleen; Gupta, Shalini; Samadi, Fahad M.; Baghel, Shilpi
Rhabdomyosarcoma with TFCP2 rearrangement is a newly introduced spindle cell neoplasm showing predilection for craniofacial bones exhibiting highly aggressive nature and poor prognosis. Therefore, an attempt was made to delineate the entity for improved understanding and treatment outcomes through comprehensive analysis of the clinicopathological and molecular characteristics. An electronic search was carried out using MEDLINE by PubMed, Scopus, Google scholar, Cochrane library, and EMBASE databases. Original articles and case reports involving intraosseous rhabdomyosarcoma arising in head and neck region with TFCP2 fusion were included. Data were compiled and risk of bias was analyzed using JBI tool. Thirteen eligible articles were included for the quantitative analysis, which revealed 33 cases with TFCP2 fusion. Majority of the affected individuals were females (58%) with mandible being the common site. Most of the patients died within few months after diagnosis demonstrating a low mean survival rate (30 months). Odds ratio, overall survival and disease-free survival were calculated and analyzed statistically concluding that intraosseous rhabdomyosarcomas harboring TFCP2 fusion are found to be novel and dreadful neoplasms. The predilection for young age with poor prognosis exhibited by these lesions demand early diagnosis and specific treatment planning to curtail mortality.